Alternatif Kebijakan Operasional Audit Maternal Perinatal (AMP) Di Kabupaten Barito Kuala Kalimantan Selatan - Mardiah Mardiah; Hedy Hardiana (HB PRESS, 2018)
Maternal Mortality Rate (MMR) is a benchmark for assessing the good health of mother and child. Given the high rate of MMR and Infant Mortality Rate (IMR) in Barito Kuala District, a Maternal Perinatal Audit (MPA) program was established at the district level with the issuance of the Bupati Decree Number 188.45/142/KUM/2015 on the establishment of the PMA Team at Barito Kuala District. The implementation of the problem was found: the legality of the clear PMA health program, the lack of human resources, the lack of facilities for health infrastructure, unequal access to health services for land and air transportation areas, limited health sector budget funds and the absence of health education institutions. Based on this, the AMP program in Barito Kuala District requires monitoring and evaluation in the effort to reduce MMR and IMR. The purpose of this study is for activities. To handle the maternal audit activities and the number of perinatal deaths in Barito Kuala District Health Office. This research use qualitative research method with case study interview with 10 informant with instrument. From the available Errors available for alternative programs required by SOPs that adapt to the natural conditions of Barito Kuala, create a Sistercity concept, a floating PONED-based puskesmas community health program for difficult terrain access areas.